2000
DOI: 10.1074/jbc.275.19.14423
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent Sequential Binding Model of a Bacillus thuringiensis Toxin to Gypsy Moth Aminopeptidase N Receptor

Abstract: Specificity for target insects of Bacillus thuringiensisinsecticidal Cry toxins is largely determined by toxin affinity for insect midgut receptors. The mode of binding for one such toxin-receptor complex was investigated by extensive toxin mutagenesis, followed by realtime receptor binding analysis using an optical biosensor (BIAcore). Wild-type Cry1Ac, a three-domain, lepidopteran-specific toxin, bound purified gypsy moth (Lymantria dispar) aminopeptidase N (APN) biphasically. Site 1 displayed fast associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
143
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(148 citation statements)
references
References 64 publications
3
143
1
1
Order By: Relevance
“…Mutagenesis studies of Cry1Ab and Cry1Ac loop 3 previously performed indicated that this amino acid region was important for binding with M. sexta BBMV and toxicity (40,41). In addition, alanine substitutions of loop 3 residues in Cry1Ab and Cry1Ac toxins showed a correlative effect on APN binding, suggesting that their effects on toxicity were due to defects in this binding (22,23). However, it was also shown that loop 3 is the cognate bind- (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutagenesis studies of Cry1Ab and Cry1Ac loop 3 previously performed indicated that this amino acid region was important for binding with M. sexta BBMV and toxicity (40,41). In addition, alanine substitutions of loop 3 residues in Cry1Ab and Cry1Ac toxins showed a correlative effect on APN binding, suggesting that their effects on toxicity were due to defects in this binding (22,23). However, it was also shown that loop 3 is the cognate bind- (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Also, recent reports indicate that the region ␤16 -␤22 located in domain III of Cry1Aa and Cry1Ab toxins is involved in the interaction with B. mori and M. sexta APNs, respectively (16,21). In addition, domain II is involved in Cry1A toxin interaction with APN because mutations in domain II loop regions that affected toxicity were shown to affect binding of Cry1Ac or Cry1Ab to M. sexta and Lymantria dispar APNs (22,23). It is important to mention that these binding studies were performed with monomeric toxins, and these mutations could also affect binding to the cadherin receptor.…”
mentioning
confidence: 99%
“…Also, we analyzed the binding of Cry1Ab mutants located in regions of domain II and domain III previously characterized as APN-binding epitopes (27,28). Our data suggest that both APN and ALP are functional receptor molecules that bind the oligomeric structure of Cry1Ab toxin with high affinity, facilitating membrane insertion and pore formation, and we also found that ALP may a have a predominant and more important role in Cry1Ab toxicity at earlier stages of larval development.…”
mentioning
confidence: 88%
“…The BBMV proteins that were solubilized with CHAPS as stated above were concentrated by Amicon YM-50 ultrafiltration, and a 2-ml aliquot was applied to a HR 5/10 Mono Q (GE Healthcare) column equilibrated with 20 mM Tris-HCl pH 8.5 buffer containing 2 mM MgCl 2 , 2 mM KCl (28,30). The column was eluted with a gradient of NaCl (0.5-1 M) with a flow rate of 1 ml/min for 40 min.…”
Section: Methodsmentioning
confidence: 99%
“…Su tamaño varía de 90-170 kDa y están unidas a la membrana celular, en concreto a las regiones denominadas "balsas lipídicas", mediante anclajes de glicosil fosfatidil inositol (GPI) (Pigott y Ellar, 2007). Las APNs han sido identificadas como sitios de unión de toxinas Cry en varias especies de lepidópteros (Candas et al, 2003;Jenkins et al, 2000;Knight et al, 1994;Luo et al, 1997;McNall y Adang, 2003;Yaoi et al, 1997) El conocimiento de la secuencia y la estructura de algunas proteínas Cry (ver apartado 1.2.1.3) ha permitido adquirir mucha información acerca de la participación de cada uno de los dominios en el mecanismo de acción. El dominio II es el dominio estructuralmente más variable en las toxinas estudiadas (Boonserm et al, 2005), por ello es considerado un factor determinante de la especificidad de las toxinas Cry (Pigott y Ellar, 2007).…”
Section: Segunda Faseunclassified